Meningothelial Meningioma Component in a Prepubertal Testicular Teratoma - Ruchi Sinha; Madhu Kumari; Ranwir Kumar Sinha; Bindey Kumar (Case Reports in Pathology)
Teratomas are nonseminomatous germ cell tumors composed of elements derived from more than one germinal layers (endoderm, mesoderm, and ectoderm). Malignant transformation of teratoma in the testis is well known; however, benign somatic neoplasm arising in a testicular teratoma is a rare occurrence. We report a case of meningothelial variant of meningioma arising in a pure and mature teratoma of the testis in a 5-year-old boy. Immunohistochemistry was positive for epithelial membrane antigen and vimentin. To our knowledge, this is the first report of meningothelial meningioma in a prepubertal testicular teratoma.